2012
DOI: 10.1021/ol3008149
|View full text |Cite
|
Sign up to set email alerts
|

Aphanamixoid A, a Potent Defensive Limonoid, with a New Carbon Skeleton from Aphanamixis polystachya

Abstract: Aphanamixoid A (1), a limonoid with a new carbon skeleton, along with its biogenetically related limonoid aphanamixoid B (2), was isolated from the leaves and twigs of Aphanamixis polystachya . Their structures with the absolute stereochemistry were determined by spectroscopic analysis, X-ray crystallography and computational methods. The significant antifeedant activity of 1 against the generalist plant-feeding insect Helicoverpa armigera (EC50 = 0.015 μmol/cm(2)) suggested it may be a potent defensive compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Recently, unprecedented quassinoids and limonoid derivatives with notable biological properties have been discovered and evaluated by our group141516. As part of our continuous effort to search for bioactive natural products17181920, two new 16-nor limonoids, harperspinoids A and B ( 1 and 2 ), with a unique 7/5/5/6/5 ring system, as well as a known one, Harperforin G ( 3 ), were isolated from the aerial parts of the title plant (Fig. 1).…”
mentioning
confidence: 99%
“…Recently, unprecedented quassinoids and limonoid derivatives with notable biological properties have been discovered and evaluated by our group141516. As part of our continuous effort to search for bioactive natural products17181920, two new 16-nor limonoids, harperspinoids A and B ( 1 and 2 ), with a unique 7/5/5/6/5 ring system, as well as a known one, Harperforin G ( 3 ), were isolated from the aerial parts of the title plant (Fig. 1).…”
mentioning
confidence: 99%
“…The two new limonoids 1 and 2 displayed promising antifeedant activity against Spodoptera exigua with EC 50 values of 25.1 and 17.3 μg/cm 2 , respectively, which were less active than that of the positive control (EC 50  = 3.7 μg/cm 2 ), a commericial neem oil containing 1 % azadirachtin, while slightly more active than aphanamixoid A (EC 50  = 25.8 μg/cm 2 ), a potential natural product with antifeedant activity [28]. Furthermore, both compounds 1 and 2 , together with the known lignan, phyllanthusmin C, showed moderate cytotoxicity against the ECA109 cell line, with the IC 50 values of 11.5, 8.5, and 7.8 μM, respectively, compared to the positive control, 17-AAG (IC 50  = 1.1 μM).…”
Section: Resultsmentioning
confidence: 99%
“…Limonoids have a broad range of bioactivities including insecticidal, antibacterial, antifungal, antimalarial, and antiviral, but are best-known as insect antifeedants, e.g., azadirachtin from the neem tree (Fang et al, 2011;Tan and Luo, 2011). Recently, aphanamixoid A, a novel skeleton limonoid that may be derived from an analogy of aphanamixoid B via 3,3-rearrangement ( Figure 6), was found to be a potent antifeedant against Helicoverpa armigera (Cai et al, 2012). For the first time, the Hao laboratory reported that some limonoids are potent activators of plant-induced SAR.…”
Section: Limonoids Activate Plant Sar and Inhibit Tmvmentioning
confidence: 99%